Rational Inefficiency, Adjustment Costs and Sequential Technologies - Benjamin Hampf (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2016)
In this paper we propose a novel approach to estimate the rational inefficiency of decision making units in the presence of adjustment costs. Using sequential definitions of the production technology, we show how cost inefficiency can be decomposed into rational and residual inefficiency as well as inefficiency caused by technical change. Furthermore, we estimate lower bounds for the unobserved adjustment costs based on unexploited cost reductions due to rational inefficiency. These adjustment costs are used to evaluate the feasibility of exploiting cost reductions caused by residual inefficiency. We demonstrate the empirical applicability of our model by estimating and decomposing the cost inefficiency of U.S. coal-fired power plants using panel data which cover the period between 1994 and 2009.
Keywords: D24; L20; O33; 330